Abscopal effects of thoracic X-ray radiation on spermatogenesis in mice - Lai, Pan-Pan; Jing, Yun-Tao; Guo, Ling; Qin, Tong-Zhou; Xue, Yi-Zhe; Zhang, Zhao-Wen; Wang, Xing; Miao, Xia; Zhang, Wei; Ding, Gui-Rong (Frontiers in Physiology, 2022)
The study aimed to elucidate abscopal effects of thoracic X-ray irradiation on spermatogenesis in mice. Male C57BL/6 mice were randomly divided into sham group and radiation group, and subjected to thorax fractionated X-ray irradiation or sham irradiation with the total dose of 5 Gy/day for each animal for 4 consecutive days. After irradiation, sperm morphology was observed, and sperm number was counted under microscope, and sperm apoptosis was detected by flow cytometry. Meanwhile, testis index was calculated, testicular morphology was observed using haematoxylin-eosin (HE) staining, and testicular ultrastructure was observed under transmission electron microscopy. The permeability of blood-testis barrier (BTB) was detected by Evans Blue fluorescence colorimetry. The protein levels of Bcl-2 associated X protein (Bax), B-cell leukemia-lymphoma-2 (Bcl-2) and Cleaved caspase 3, promyelocytic leukaemia zinc finger (PLZF) and c-kit proto-oncogene (c-kit) in testes were determined by western blotting (WB). The location of apoptotic cells was confirmed by terminal deoxynucleotidyl transferase (TdT) enzymaticated dUTP nick end labelling (TUNEL) assay. The levels of tumor necrosis factor alpha (TNF-α), transforming growth factor-β1 (TGF-β1), interleukin 10 (IL-10) were measured by enzyme-linked immunosorbent assay (ELISA). The levels of Total superoxide dismutase (T-SOD) and malondialdehyde (MDA) were measured by the biochemical assay kit. Compared with sham group, the sperm quality of mice in radiation group showed decreased number and survival rate, along with increased abnormality and total apoptosis rate. The testis index of irradiated mice was lower, the testicular apoptosis was increased, and their testicular histology and ultrastructure was severely damaged. The permeability of BTB was increased, the level of PLZF in testis was decreased, and the level of c-kit was increased by irradiation. After irradiation, the levels of TNF-α, TGF-β1, IL-10, T-SOD and MDA in testes were significantly changed. Taken together, abscopal effects of thoracic X-ray irradiation on spermatogenesis were obvious, which could decrease sperm quality and damage testicular morphology and increase the permeability of BTB, and a series of inflammation and oxidative stress factors were involved in the process. These findings provide novel insights into prevention and treatment for male reproductive damage induced by clinical thoracic irradiation.